2001
DOI: 10.1089/10766290152652783
|View full text |Cite
|
Sign up to set email alerts
|

Low Prevalence of Methicillin-Resistant Strains amongStaphylococcus aureusColonizing Young and Healthy Members of the Community in Portugal

Abstract: Recent reports suggest that methicillin-resistant Staphylococcus aureus (MRSA) may be emerging as a community pathogen. In Portuguese hospitals, the incidence of MRSA among disease causing isolates is extremely high (48-50%). To determine the prevalence of MRSA in the Portuguese community, nasal samples were obtained from 823 draftees, 484 nonmedical university students, and 107 high-school students. In addition, throat samples were obtained from the 823 draftees and S. aureus isolates were also recovered from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
50
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 42 publications
8
50
2
Order By: Relevance
“…5%) [12]. This frequency was similar to that obtained from studies performed in the United States, Portugal and Italy, all of which reported carriage rates of less than 1 % [13][14][15]. Although the importance of the community as a source of MRSA infections has not been determined, this change in pattern of occurrence may require modifications in hospital infection control programmes.…”
Section: Introductionsupporting
confidence: 84%
“…5%) [12]. This frequency was similar to that obtained from studies performed in the United States, Portugal and Italy, all of which reported carriage rates of less than 1 % [13][14][15]. Although the importance of the community as a source of MRSA infections has not been determined, this change in pattern of occurrence may require modifications in hospital infection control programmes.…”
Section: Introductionsupporting
confidence: 84%
“…ST1 and ST8 represented minor clones, but ST30, which was initially described among CA-MRSA in Australia and recently reported to have spread in the community in Europe both in The Netherlands and in Latvia (22,35), corresponded to the main clone found in the present study. In addition, the background of the only two true CA-MRSA strains described so far in Portugal (30) was not found among the MSSA nasal carriage population in our work that in part overlaps the S. aureus isolates from the Sa-Leão et al study (30). Apparently, as happened with the major hospital-acquired MRSA, we anticipate CA-MRSA ST82 was probably imported from abroad.…”
Section: Discussionmentioning
confidence: 45%
“…Although reports of community-acquired MRSA (CA-MRSA) are increasing worldwide, the single study evaluating the prevalence of MRSA among the Portuguese community revealed a low carriage rate (Ͻ1%) (30). In that study, the two out of seven CA-MRSA isolates not healthcare associated produced enterotoxins A and B and were both ST82.…”
mentioning
confidence: 86%
“…Previous studies dated from 1996 to 2009, including isolates from nasal swabs of young healthy individuals and nasopharyngeal swabs of children attending day care centers, reported an MRSA prevalence lower than 0.25% in the Portuguese healthy community (0.24% in 1996-1998 and 0.13% in [2006][2007][2008][2009] [6,9,10].…”
mentioning
confidence: 99%